Increased matrix metalloproteinase-9 in male elderly with low 25-hydroxy-vitamin D - Pusparini, Pusparini; Merijanti, Lie Tanu; Sudharma, Novia I. (Faculty of Medicine, Trisakti University, 2016)
Background One of the extra-skeletal roles of vitamin D for health is associated with cardiovascular disease. Poor vitamin D status has been associated with vascular endothelial dysfunction. There were controversial results about the association between vitamin D deficiency and matrix metalloproteinaseÂ 9 (MMP-9) concentration. The purpose of the present study was to determine the concentrations of 25(OH) vitamin D [25(OH)D] in an elderly population and to find any association between 25(OH)D and MMP-9 concentrations.MethodsThis study was of cross-sectional design involving 160 male and female subjects aged 55â€“65 years, in South Jakarta, Indonesia. Determination of MMP-9 and 25(OH)D concentrations was done concurrently on subjects who met the inclusion and exclusion criteria after all study subjects had been selected. 25(OH)D and MMP-9 concentrations were assessed by direct competitive chemiluminescence immunoassay (CLIA) and enzyme-linked immunosorbent assay (ELISA) respectively. Statistical analysis used chi square and t tests.ResultsMean 25(OH)D concentration in the study subjects was 14.4 Â± 6.4 ng/mL. A total of 68.8% of subjects had a 25(OH)D level of <20 ng/mL, and 31.2 % had a 25(OH)D level of >20 ng/mL.There was an increased MMP-9 concentration in male subjects with a 25(OH)D level of <20 ng/mL compared with subjects with 25(OH)D level of >20 ng/mL (p=0.011), but not among female subjects (p=0.809).ConclusionThe MMP-9 concentration was increased among male subjects with low level of (OH)D. This study confirmed that 25(OH)D concentration may have a potential role in endothelial function.